VAT Attacks! - Keen, Michael (IMF Working Papers; Working Paper ;, 2007)
Like the theory of the second best that the 2006 congress marks, the VAT is now fifty years old. Judged by the extent and speed of its spread around the world, and the revenue that it raises, the VAT would seem to have been a remarkable success. Over the last few years, however, it has come under a series of attacks. This paper considers three of the most prominent of these. One is the fear (raised mainly in the United States) that the VAT actually does too good a job of raising tax revenue. The second is the view that the VAT does a bad job of taxing the informal sector-and that tariffs might be a better revenue-raising instrument for many developing countries. The third attack is the most literal, by criminals rather than theorists: in the European Union and elsewhere, sophisticated VAT fraud, targeting its refund provisions, has become a serious concern.